2012
DOI: 10.2174/157488612805076606
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Evaluation of the Dosing Regimen of Vancomycin in Children of Different Weight Categories

Abstract: PK properties of all weight groups were similar. More frequent and higher doses are needed to achieve the goals of current guidelines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 32 publications
1
15
0
Order By: Relevance
“…37 Consistent with previous studies, our study found that the weight-adjusted V d and CL decreased by 2.2% and 10.8%, respectively, in obese and overweight children compared with those with normal weight. One potential explanation for the small decrease in weight-adjusted V d is the hydrophilicity of and large size of vancomycin, which hinders drug distribution into adipose tissue.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…37 Consistent with previous studies, our study found that the weight-adjusted V d and CL decreased by 2.2% and 10.8%, respectively, in obese and overweight children compared with those with normal weight. One potential explanation for the small decrease in weight-adjusted V d is the hydrophilicity of and large size of vancomycin, which hinders drug distribution into adipose tissue.…”
Section: Discussionsupporting
confidence: 92%
“…One pediatric study found no statistical difference between different weight groups for weight-adjusted V d and CL. 3 In our study, we incorporated SCr, age, and ALWT for CL estimation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The remaining 20 publications contained PK data for 21 drugs, including 7 anti-neoplastic drugs, 4 anticonvulsants, 4 antibiotics, 3 analgesic/anesthetic drugs, 2 respiratory stimulants, and 1 immunosuppressant (Table 1). Six out of 21 (29%) drugs were not studied in a formal prospective PK trial (gentamicin 29 ; vancomycin 17,18,30 ; valproic acid 19 ; divalproex sodium 20 ; busulfan 21 ; and cyclosporine 36 ). PK data for these studies were collected following drug administration per standard of care, frequently with sparse sampling.…”
Section: Resultsmentioning
confidence: 99%
“…Vancomycin is perhaps the most studied antimicrobial agent in obese children and adults . PK studies suggest a strong correlation between Vd and Cl with TBW in obese adults .…”
Section: Methodsmentioning
confidence: 99%